PERCUTANEOUS PINNING IN DISPLACED SUPRACONDYLAR FRACTURE OF HUMERUS IN CHILDREN - Shoaib, Muhammad; Sultan, Shahid; Sahibzada, Sohail Ahmed; Ali, Azmat (Journal of Ayub Medical College Abbottabad, 2004)
Background: Supracondylar fracture of humerus is the most common fracture in first decade of life. There are various treatment modalities for this fracture i.e closed reduction and casting, open reduction and internal fixation and percutaneous pinning. Study was conducted to know the outcome of Percutaneous Pinning in the management of displaced supracondylar fracture of humerus in children. Methods: This study was conducted at orthopedic unit of Khyber Teaching Hospital Peshawar from January 1996 to December 2000. Twenty children of 3-12 years age with displaced supracondylar fracture (Gartland type II & III) of humerus were included. Outcome measures were according to Flynn criteria i.e loss of elbow motion & carrying angle. Results: The children presenting were 14 male (70%) and 6 females (30%).The involved side was left in fifteen (75%) and right in five (25%) of patients. Nineteen patients (95%) had extension type & one patient (5%) had flexion type of fracture. Gartland type II were six (30%) & type III were fourteen (70%). Our result showed excellent outcome in thirteen (65 %), good outcome in four (20 %) and poor outcome in three (15 %) patients. Conclusion: Percutaneous pinning is safe, cost effective, time saving and provides greater skeletal stability with excellent results. Key Words: Percutaneous Pinning, Supracondylar fracture, Humerus fractures.